2016
DOI: 10.4039/tce.2016.16
|View full text |Cite
|
Sign up to set email alerts
|

Apple cultivar preferences byHoplocampa testudinea(Hymenoptera: Tenthredinidae) in the Annapolis Valley of Nova Scotia, Canada

Abstract: The European apple sawfly, Hoplocampa testudinea (Klug) (Hymenoptera: Tenthredinidae), is an economically important pest in eastern Canada. Growers can experience significant crop losses as management of this species is difficult because it is present during bloom. As a result, management strategies other than pesticides are required for this pest. Eleven commercial and experimental apple (Malus pumila Miller; Rosaceae) cultivars were studied to evaluate host resistance as a potential management strategy. Pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Mentions of M. pumila as a host (e.g. Burgart et al 2016) seem to involve cultivated varieties more usually referred to as M. domestica. Pyrus communis is apparently a rarely used, secondary host (Stritt 1943).…”
Section: Hoplocampa Minuta (Christ 1791)mentioning
confidence: 99%
“…Mentions of M. pumila as a host (e.g. Burgart et al 2016) seem to involve cultivated varieties more usually referred to as M. domestica. Pyrus communis is apparently a rarely used, secondary host (Stritt 1943).…”
Section: Hoplocampa Minuta (Christ 1791)mentioning
confidence: 99%
“…Results from our study provided only weak support (r = 0.4 and 0.2) for the preference-performance hypothesis. Hoplocampa testudinea females did not randomly oviposit across cultivar across multiple years, suggesting an orientation to cultivar based upon chemical cues [ 22 ], as observed for the apple blossom weevil [ 43 ] or possibly visual cues associated with the apple blossom [ 44 ]. However, the cultivar preference observed during oviposition in this study ranks the cultivars differently than is observed at harvest (see Table 1 and Table 2 ), further supporting the hypothesis that larval performance during development is contributing to observed results at harvest.…”
Section: Discussionmentioning
confidence: 99%
“…Cultivar preference in H. testudinea is not a novel idea. Briggs and Alston [ 19 ], Alford [ 20 ], Hogmire and Miller [ 21 ] and Burgart [ 22 ] all suggested that H. testudinea prefers certain cultivars, based upon observed damage assessments conducted at harvest. Burgart [ 22 ] found preferred cultivars early in the season (based upon adult visitation during bloom, when oviposition is occurring) to be different from the ranking observed during fruitlet development (based upon visual surveys of infested fruitlets) and again different from the ranking observed at harvest (based on observed damage).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…= Nematus zebratus (Kincaid, 1900) - AK --------------- Kincaid 1900 Genus Fallocampus Wong, 1977 Key to Nearctic species (as Platycampus) -Smith 1976b F. albostigmus (Rohwer, 1908) CAN AK -NT -BC AB SK MB ON ---NS --- Smith 1976b;Wong 1977;Smith 1979a F. americanus (Marlatt, 1896) CAN AK ----AB --ON QC NB ----- Smith 1976b Genus Hemichroa Stephens, 1835 H. alpestris Rohwer, 1911 CAN ----BC AB ---------- Ross 1943c H. bioculata Rohwer, 1908 CAN ----BC AB ----------H. brevis (Klug, 1816) § CAN --------ON -------H. cookei (Clarke, 1906) CAN ----BC -----------INHS H. halcyon (Norton, 1861) CAN ----BC AB SK MB ON QC NB -NS --- Smith 1979a;Goulet 1987 H. lacteipennis Rohwer, 1910 CAN -----AB SK MB ON QC ------Ross 1943c H. marlatti Rohwer, 1911 CAN -----AB -MB --NB -NS ---Smith 1979a H. montanicola Rohwer, 1911 CAN ----BC AB SK MB ON QC ------Ross 1943c H. neneti Ross, 1943 CAN --------ON -------H. pallipes MacGillivray, 1893 CAN ----BC AB ----------Ross 1943c H. spala Ross, 1943 CAN ----BC -----------Ross 1943c H. stricklandi Ross, 1943 CAN -----AB ----------H. testudinea (Klug, 1816) § Note: apparently eradicated in BC (Vincent et al 2019) CAN ----BC ---ON QC --NS --- Vincent et al 2013;Burgart et al 2016 P. elaphita Wong & Ross, 1960…”
Section: Can Ak Yt -Nu Bc Ab -Mb On ---Ns ---mentioning
confidence: 99%